Early graft losses in paired kidney exchange: Experience from 10 years of the National Kidney Registry. Issue 5 (29th January 2020) - Verbesey, Jennifer; Thomas, Alvin G.; Ronin, Matt; Beaumont, Jennifer; Waterman, Amy; Segev, Dorry L.; Flechner, Stuart M.; Cooper, Matthew
Abstract : Cooperative kidney paired donation (KPD) networks account for an increasing proportion of all living donor kidney transplants in the United States. There are sparse data on the rate of primary nonfunction (PNF) losses and their consequences within KPD networks. We studied National Kidney Registry (NKR) transplants (February 14, 2009 to December 31, 2017) and quantified PNF, graft loss within 30 days of transplantation, and graft losses in the first‐year posttransplant and assessed potential risk factors. Of 2364 transplants, there were 38 grafts (1.6%) lost within the first year, 13 (0.5%) with PNF. When compared to functioning grafts, there were no clinically significant differences in blood type compatibility, degree of HLA mismatch, number of veins/arteries, cold ischemia, and travel times. Of 13 PNF cases, 2 were due to early venous thrombosis, 2 to arterial thrombosis, and 2 to failure of desensitization and development of antibody‐mediated rejection (AMR). Given the low rate of PNF, the NKR created a policy to allocate chain‐end kidneys to recipients with PNF following event review and attributable to surgical issues of donor nephrectomy. It is expected that demonstration of low incidence of poor early graft outcomes and the presence of a "safety net" would further encourage program participation in national KPD. Abstract : This study quantifies the low rate of primary nonfunction outcomes in national kidney paired exchange and describes a new policy that allocates chain‐end kidneys to recipients with primary nonfunction to further encourage program participation in national paired exchange. Kulkarni and Ladin's editorial is on page 1223 .